An evaluation of hyperbaric ropivacaine with magnesium as an adjuvant in lower abdominal surgeries among the north Indian subjects: a double-blind randomized trial - Saxena, Sulekha; Kumar, Kuljit; Gupta, Rajni; Agrawal, Avinash (International Journal of Research in Medical Sciences, 2019)
Background: An evaluation of intrathecal hyperbaric ropivacaine without adjuvant and with adjuvant magnesium for lower abdominal surgeries. Methods: This was a prospective, randomized, double-blind study conducted among the patients aged 18 to 60 years planned for lower abdomen surgeries under spinal anaesthesia and ASA grade I or II. Patients were randomly allocated to two groups (30 in each): ropivacaine Group (R group): spinal anesthesia with 3ml of 0.6% hyperbaric ropivacaine (18mg )+ 0.5ml NS. hyperbaric ropivacaine + Magnesium Group (R+M group ): spinal anesthesia with 3ml of 0.6% hyperbaric ropivacaine (18mg) + 0.5ml magnesium sulphate (50 mg). All the patients scheduled for operation were given oral tablets ranitidine 150 mg and Alprazolam 0.25mg in the night before surgery. Results: There was no significant difference in the basic characteristics between the groups. The mean HR, MAP and SpO2 in both the groups decreased over the periods as compared to baseline. However, the trend of HR over the periods remains similar in both R and R+M groups. The bromage levels were significantly (p=0.0001) higher among the patients of Group R compared with R+M. The 2 segment sensory regression (min), Sensory regression S2 (hr), motor recovery (hrs) and long term mobilization after spinal anesthesia were significantly (p=0.0001) lower among the patients of Group R compared with R+M. The complications were lower in Group R+M than R. Conclusions: Magnesium may be more suitable drug in surgeries in which muscle relaxation has greater value in lower abdominal surgeries.